FAKTOR-FAKTOR YANG MEMPENGARUHI BELANJA MODAL DENGAN PERTUMBUHAN EKONOMI SEBAGAI VARIABEL PEMODERASI (Studi Empiris Pada Kab/Kota Provinsi Jawa Tengah Periode 2013-2015) - Noora Fahrunisah, 14.05.52.0044; Badjuri, Achmad (Students Journal of Accounting and Banking, 2018)
This study aimed to examines the influence of the regional revenue, general allocation funds and general special allocation funds on the capital expenditures moderated by economic growth. The population of this research are District/City Central Java Province which consists of 35 District/City. The study uses secondar data such as Realization Report 2013 until 2015 budget. The technique of data analysis is used multiple regression analysis.The results of this study shows that General Allocation Fund has a positive influence on Capital Expenditure. However, Local Revenue and Special Allocation Fund does not affect on Capital Expenditure. While Economic Growth proved to moderate Local Revenue to Capital Expenditure. But Economic Growth does not moderate the relationship between the General Allocation Fund and the Special Allocation Fund to Capital Expenditures. Keywords : Local Revenue, General Allocation Fund, Special Allocation Fund, Economic Growth and Capital Expenditure